Silvopastoral Restoration to Enhance Ecosystem Services and Increase Farmers' Income - Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2023)
The presentation delves into the multifaceted issues surrounding silvopasture degradation. It investigates the root causes, with a spotlight on the adverse impacts of climate change, improper grazing practices, and encroachment of agricultural activities. Silvopastoral systems, as a subset of agroforestry, strategically integrate woody perennials, forages, and livestock to enhance agricultural production and environmental services. The research underscores the historical factors contributing to degradation, contextualizes the significance of restoration efforts, and identifies key risks and drivers of change. Effective planning involves a comprehensive understanding of socio-cultural dynamics, land tenure structures, and the prioritization of restoration efforts. The overarching objective is to elevate the livelihoods of silvopastoral communities by bolstering resilience, increasing income, and enhancing overall capacity. A participatory multidisciplinary approach is advocated, placing a strong emphasis on community-driven restoration initiatives. Various techniques, including soil and water conservation, thoughtful species selection, and the incorporation of indigenous, well-adapted varieties, are discussed. Specific species, such as Hedysarum coronarium and Opuntia ficus indica, are recommended for their notable attributes, including drought resistance, soil improvement, and high fodder potential.